Bifunctional Co3S4 Nanowires for Robust Sulfion Oxidation and Hydrogen Generation with Low Power Consumption. (8th December 2022) - Xiao, Zehao; Lu, Chang; Wang, Jie; Qian, Yinyin; Wang, Bowen; Zhang, Qiang; Tang, Aidong; Yang, Huaming
Abstract: Sulfion oxidation reaction holds great potential for replacing kinetically sluggish water oxidation to save power consumption and simultaneously purifying environmental sulfion‐rich sewage. However, it is still challenged by the insufficient mechanism understanding and questionable stability caused by sulfur passivation. Here, it is demonstrated that bifunctional Co3 S4 nanowires for assembling hybrid seawater electrolyzer that combines anodic sulfion oxidation and cathodic seawater reduction with an ultra‐low power consumption of 1.185 kWh m −3  H2 under 100 mA cm −2, saving energy consumption over 70% compared to the traditional water splitting system. Unlike water is oxidized into O2 at high potentials under alkaline water splitting system, experiments combined with in situ characterizations uncover the stepwise oxidation of S 2− to short‐chain polysulfides and then to value‐added product of S8 . Density functional theory calculations prove that Co3 S4 possesses reduced energy barriers in the rate‐determining S3 2− to S4 − oxidation step and S8 desorption step, promoting conversion of short‐chain polysulfides and efficient desorption of S8 . These findings reveal the catalytic mechanism of sulfion oxidation and inspire an economic approach toward the fabrication of bifunctional Co3 S4 for achieving energy‐saving hydrogen production from seawater while rapidly disposing sulfion‐rich sewage with boosted activity and stability. Abstract : Bifunctional Co3 S4 nanowires are employed for assembling hybrid seawater electrolyzer that combines anodic sulfion oxidation and cathodic seawater reduction with an ultra‐low power consumption of 1.185 kWh m −3 H2 under 100 mA cm −2, saving energy consumption over 70% compared to the traditional water splitting system. Experiments combined with in situ characterizations uncover the stepwise oxidation of S 2− to short‐chain polysulfides and then to value‐added product of S8 .